Physiological and transcriptomic aspects of adaptation to extreme environments - Passow, Courtney Nicole (Kansas State University, 2016)
Extremophiles are organisms with the ability to survive in environments characterized by strong physicochemical stressors lethal to most other organisms, providing excellent models to further our understanding of life's capacities and limitations to deal with far-from-average conditions. I studied how physiological processes varied among fish residing in starkly different environmental conditions to understand how organisms cope with extreme environments and disentangle the roles of short-term plastic responses and evolved population differences in shaping physiological responses. I used the Poecilia mexicana model, a series of extremophile fish populations that has colonized toxic hydrogen sulfide (H₂S) rich springs and caves, to address three major objectives: (1) I investigated the energetic consequences of life in extreme environments and tested whether predicted reductions in organismal energy demands evolved repeatedly along replicated environmental gradients. (2) I characterized variation in gene expression among populations and organs to test for interactive effects between different stressors and identify potential physiological mechanisms underlying adaptation to H₂S and cave environments. (3) I conducted common garden and H₂S-exposure experiments to test how evolutionary change and plasticity interact to shape variation in gene expression observed in nature. To address these objectives, I measured variation in metabolic physiology and quantified variation in physiological processes through genome-wide gene expression analyses. I found that adaptation to extreme environments directly impacts energy metabolism, with fish living in extreme environments consistently expending less energy overall. Reductions in energy demand have evolved in convergence and were primarily mediated through a life history shift (reduction in body mass). The quantification of gene expression across divergent habitats and organs revealed organ-specific physiological responses in H₂S-rich and cave habitats. Gene expression variation in the relevant genes was primarily shaped by evolutionary change in gene regulation, and ancestral plastic responses play a minor role in causing the observed expression differences between replicated sulfidic and nonsulfidic populations in nature. Overall, my research has implications for understanding the capacities and constraints that shape life in extreme environments and aids in our understanding of modifications in physiological pathways mediating adaptation to elevated H₂S and perpetual darkness.
Keywords: Local adaptation; Metabolic physiology; Evolutionary ecology; Gene expression; Hydrogen sulfide; Cave adaptation